Miners' strike, 1972 (London, 1972)
1972 1970-74 "Miners' strike, 1972" [BW0051], 1972, Trades Union Congress This strike, January 9 - February 28, 1972, arose from a dispute between the National Union of Mineworkers and the Conservative Government over pay. The miners began to picket coal-fired power stations, later extended to all power stations, steelworks, ports and other major coal users. On February 9, a state of emergency was declared and a three-day working week began two days later to save electricity and coal supplies. From February 16, electricity was switched off on a rota basis between 0700 and 2400 every day. A committee of inquiry under Lord Wilberforce recommended a pay increase and agreement was reached between the NUM and the Government on February 19. Picketing was then called off and on February 25, the miners accepted an increased pay offer in a ballot. This is a special ballot issue of The Miner, February 21, 1972.